The role of the town clerk in municipal government in South Africa - Craythorne, Donald L (Department of Political Studies, 2016)
The purpose of this thesis is to study the role the Town Clerk plays in South African municipal government and to suggest what that role could be. The thesis is not concerned with politics as such but with public administration, although because of the structure of local government, the Town Clerk is involved with politics in the sense that the lay-administrators he works with are politicians. It is stressed that politics does not mean party politics. Furthermore, while the Town Clerk forms the central theme of the thesis, his role cannot be discussed in isolation from the local government system within which he operates.